(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2019)
Cyanide is extremely toxic to living organisms. It is utilized in industries for gold and silver extraction, pharmaceuticals, plastic processing, electroplating, and agricultural chemistry. Cyanide can persevere for a long time in the soil and its bio-degradation is the best economical practice. A formerly isolated cyanide-degrading bacterium Azotobacter vinelandii exhibited substrate inhibition to degradation rate. Significant degradation inhibition constants were achieved reliably by means of non-linear regression modeling of the degradation rate profile utilizing models for substrate inhibition like Haldane, Teissier-Edward, Monod, Yano and Koga, Luong, Edward (Webb) Luong and Aiba models. Aiba model was selected as the top model established on statistical assessments like root mean square error, adjusted coefficient of determination, bias factor and accuracy factor. The calculated values for the Aiba constants qmax (the maximum specific substrate degradation rate (hâˆ’1), Ks (concentration of substrate at the half maximal degradation rate (mM) and Ki (inhibition constant (mM)) were 0.060 (95% CI, 0.024 to 0.096), 0.302 (95% CI, 0.381 to 0.222) and 0.953 (95% CI, 0.568 to 1.338), respectively. The novel constants gotten from the modeling application can be valuable for advanced secondary modeling implicating the influence of media conditions and some other dynamics on cyanide biodegradation by this bacterium.